Nutrient release to oceans from buoyancy-driven upwelling at Greenland tidewater glaciers. Issue 1 (January 2019) - Cape, Mattias; Straneo, Fiammetta; Beaird, Nicholas; Bundy, Randelle; Charette, Matthew
Abstract The discharge of nutrient-rich meltwater from the Greenland Ice Sheet has emerged as a potentially important contributor to regional marine primary production and nutrient cycling. While significant, this direct nutrient input by the ice sheet may be secondary to the upwelling of deep-ocean-sourced nutrients driven by the release of meltwater at depth in glacial fjords. Here, we present a comprehensive suite of micro- and macronutrient observations collected in Sermilik Fjord at the margin of Helheim, one of Greenland's largest glaciers, and quantitatively decompose glacial and ocean contributions to fjord dissolved nutrient inventories. We show that the substantial enrichment in nitrate, phosphate and silicate observed in the upper 250 m of the glacial fjord is the result of upwelling of warm subtropical waters present at depth throughout the fjord. These nutrient-enriched fjord waters are subsequently exported subsurface to the continental shelf. The upwelled nutrient transport within Sermilik rivals exports by the largest Arctic rivers and the ice sheet as a whole, suggesting that glacier-induced pumping of deep nutrients may constitute a major source of macronutrients to the surrounding coastal ocean. The importance of this mechanism is likely to grow given projected increases in surface melt of the ice sheet. Glacial meltwater from the Greenland Ice Sheet causes buoyancy-driven upwelling of nutrient-rich, subtropical waters from depth to the continental shelf. This nutrient transport may exceed the direct ice sheet inputs, according to geochemical analyses of transect samples from Sermilik Fjord.